Every Business is a Growth Business: How Your Company Can Prosper Year After Year - Ram Charan; Noel M. Tichy (Great Britain John Wiley & Sons, 1998)
After the downsizing, re-engineering and streamlining trend of the past two decades, there has been a renewed interest in growth. Mergers and acquisitions are playing a key role in the battle for market share, but share alone cannot secure a company's future. This text argues that truly sustained growth can only be achieved through a new way of thinking. The author's set out a framework based on five keys: there is no such thing as a mature business; not all growth is good; growth is a mentality created by a company's leadership; balanced growth is the key to prosperity in the 21st century; and growing is less risky than not growing.
Age Group: Adult
Includes Index
Keywords: Business